Vulvar Myiasis Complicating Condyloma Acuminata In Pregnancy - Radotra Anuradha; Goel Poonam; Thami Gurvinder P; Aggarwal Anjali; Wanchu Madhavi; Bhalla Mala (Wolters Kluwer Medknow Publications, 2004)
A rapidly progressing conyloma acuminata infested with maggots in pregnancy at 38 weeks of gestation, is described.